Computational Social Networks 2012
DOI: 10.1007/978-1-4471-4054-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Online Social Network Data Collection

Abstract: Large quantities of information are shared through online social networks, making them attractive sources of data for social network research. When studying the usage of online social networks, these data may not describe properly users' behaviours. For instance, the data collected often include content shared by the users only, or content accessible to the researchers, hence obfuscating a large amount of data that would help understanding users' behaviours and privacy concerns. Moreover, the data collection m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Researchers have studied it by collecting the data of SNS usage behaviors as a first step [9,[14][15][16][17][18]. Many types of data and collection methods exist.…”
Section: Data Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have studied it by collecting the data of SNS usage behaviors as a first step [9,[14][15][16][17][18]. Many types of data and collection methods exist.…”
Section: Data Collectionmentioning
confidence: 99%
“…Many types of data and collection methods exist. Abdesslem et al [16] summarized the existing data collection methods as follows: 1) Self-reported data:…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations